Questioning gender : a sociological exploration - Ryle, Robyn (Pine Forge Press, 2012)
Rather than providing definitive answers about gender, this unique book exposes readers to new material that will lead them to question their assumptions. The author uses both historical and cross-cultural approaches-as well as a focus on intersectionality and transgender issues-to help students understand the socially-constructed nature of gender.